2021
DOI: 10.1038/s41598-021-91537-0
|View full text |Cite
|
Sign up to set email alerts
|

Variability in waxy (Wx) allele, in-vitro starch digestibility, glycemic response and textural behaviour of popular Northern Himalayan rice varieties

Abstract: Eight commonly cultivated and consumed rice varieties of Northern Himalayan regions and a popular high amylose rice variety were characterized at Wx locus and evaluated for resistant starch (RS), in-vitro starch digestibility, predicted glycemic index (pGI), glycemic load (GL) and textural parameters. Cytosine and thymine repeats (CT)n at waxy locus (Wx) showed high association with apparent amylose content (AAC). Both pGI and GL varied substantially within the selected varieties. The pGI was relatively lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…(2010), whereas rice with intermediate GI values were reported by Naseer et al . (2021). Rice with a low GI (<55) value was reported by Rao et al .…”
Section: Resultsmentioning
confidence: 99%
“…(2010), whereas rice with intermediate GI values were reported by Naseer et al . (2021). Rice with a low GI (<55) value was reported by Rao et al .…”
Section: Resultsmentioning
confidence: 99%
“… 16 Studies have also showed significant associations between amylose content, predicted glycemic index and glycemic load, and allelic variation linked to waxy variants. 29 , 30 More detailed studies of health outcomes and microbiome composition in populations consuming large amounts of waxy or high-amylose rice could therefore illuminate the potential for waxy rice consumption to predispose the local populations to type II diabetes. 17 , 30 More research needs to be done to determine the negative ramifications of consuming high quantities of waxy grain.…”
Section: Discussionmentioning
confidence: 99%
“…While studies of locally grown and consumed rice and sorghum are limited, recent work on locally grown and consumed rice cultivars in selected areas of Asia has shown that nearly half of the cultivars studied have low amylose content and would be considered waxy. 29 , 30 Therefore, understanding how waxy phenotypes, in the whole grain context, may influence the microbiome and host physiology is of primary interest to domestic and global health.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of the glycemic index for a broad panel of rice cultivars, including improved cultivated varieties, showed a strong association of naturallyoccurring waxy alleles with elevated glycemic index values and a signi cant negative correlation between amylose content and glycemic index rating [20]. Studies have also showed signi cant associations between amylose content, predicted glycemic index and glycemic load, and allelic variation linked to waxy variants [35,36]. More detailed studies of health outcomes and microbiome composition in populations consuming large amounts of waxy or high-amylose rice could therefore illuminate the potential for waxy rice consumption to predispose the local populations to type II diabetes [21,36].…”
Section: Discussionmentioning
confidence: 99%
“…This gap is particularly relevant in Asia and Africa, where rice and sorghum are consumed daily as whole grain staples. While studies of locally grown and consumed rice and sorghum are limited, recent work on locally grown and consumed rice cultivars in selected areas of Asia have shown that nearly half of the cultivars studied have low amylose content and would be considered waxy [35,36]. Therefore, understanding how waxy phenotypes, in the whole grain context, may in uence the microbiome and host physiology are of growing importance.…”
Section: Introductionmentioning
confidence: 99%